THE INFLUENCE OF SERVICE QUALITY AND STORE ATMOSPHERE ON CUSTOMER SATISFACTION - Miswanto, Miswanto; Angelia, Yessi Ria (Jurnal Manajemen dan Kewirausahaan, 2017)
This research examines the influence of service quality (tangibles, reliability, responsiveness, assurance, and empathy) and store atmosphere on customer satisfaction and the influence of customer satisfaction on repurchase intention, trust, and word of mouth on customers of souvenir stores in Yogyakarta. Selection of the sample is done by using purposive sampling with one criterion: they have shopped in souvenir stores in Yogyakarta. Data are collected by using questionnaires and 200 souvenir store customers participate in this study. The data are analyzed by using Structural Equation Modeling (SEM) with Amos computer program. The findings show that none of service quality’s dimension: tangibles and store atmosphere have positive influences on customer satisfaction.